Profiling of N-acetylated protein termini provides in-depth insights into the N-terminal nature of the proteome. - Helbig, A; Gauci, S; Raijmakers, R; van Breukelen, B; Slijper, M; Mohammed, S; Heck, A (2010)
N-terminal processing of proteins is a process affecting a large part of the eukaryotic proteome. Although N-terminal processing is an essential process, not many large inventories are available, in particular not for human proteins. Here we show that by using dedicated mass spectrometry-based proteomics techniques it is possible to unravel N-terminal processing in a semicomprehensive way. Our multiprotease approach led to the identification of 1391 acetylated human protein N termini in HEK293 cells and revealed that the role of the penultimate position on the cleavage efficiency by the methionine aminopeptidases is essentially conserved from Escherichia coli to human. Sequence analysis and comparisons of amino acid frequencies in the data sets of experimentally derived N-acetylated peptides from Drosophila melanogaster, Saccharomyces cerevisiae, and Halobacterium salinarum showed an exceptionally higher frequency of alanine residues at the penultimate position of human proteins, whereas the penultimate position in S. cerevisiae and H. salinarum is predominantly a serine. Genome-wide comparisons revealed that this effect is not related to protein N-terminal processing but can be traced back to characteristics of the genome.